Numerical Modeling of Air-Based Bus Seat - Tan, CheeFai; Khalil , Siti Nurhaida; Said, Md Radzai (Trans Tech Publications, 2014)
Travel with long hours will create discomfort feeling for passenger especially express bus passenger. Long hour travel will create physiological stress on passenger. It may due to seat space limitation, noise, vibration, seat hardness as well as seat comfort. Seat comfort is a subjective feeling that related to psychological aspect of passenger. In this project, the bus passenger seat is integrated with air-based and gel-based material. In Malaysia, most of the express coaches are using polyurethane foam based cushion in the seat padding. This type of the seat padding may cause a bus passenger who sit for long journey will feel uncomfortable and fatigue. There are two main causes which lead to seating discomfort which is vibration and pressure distribution on the seat. The new design a bus passenger seat is using air-based cushion to improve the seating comfort. The air-based seat was validated by using MatLab SimuLINK software. In the model validation process, the parameters of air cell height gave effect on the pressure change rate of air cushion model. The comfortable level of the air cushion could be improved by reducing the pressure change rate and cell height.